Cell-Based Therapy Of Human Adipose- Derived Mesenchymal Stem Cell Expressing Angiopoietin-1 In An Experimental Model Of Airway Inflammation - Abdul Halim, Nur Shuhaidatul Sarmiza (2018)
Cell-based therapy of mesenchymal stem cells (MSCs) has been shown to enhance the endogenous repair process by increasing the limited regenerative capacity of the lung in chronic lung disorders as well as following injury. However, the underlying cellular and molecular mechanisms of MSCs to enhance airway regeneration and repair are remain unclear. This study was aimed to investigate the effect of delivering human adipose-derived MSCs (hAD-MSCs) alone and in combination with vasculoprotective factor, the ANGPT1, by aerosol technique in a rabbit model of asthma related-airway inflammation.